Emollients to Prevent Eczema in High-Risk Infants: Integrative Review. Issue 3 (May 2022) - Armstrong, Julie; Rosinski, Nicole K.; Fial, Alissa; Ansah, Selorm; Haglund, Kristin
Abstract: The purpose of this integrative review was to assess the research on topical emollients to prevent atopic dermatitis (AD) also known as eczema, in infants at high risk for this condition. Atopic dermatitis is a common chronic inflammatory skin disorder. Skin barrier dysfunction plays a prominent role in its development. Topical emollients have been hypothesized to enhance the skin barrier and prevent AD. Methods: Searches were conducted in September 2021 in PubMed, CINAHL, Cochrane Library, and Web of Science using key word search terms dermatitis, atopic, emollients, petrolatum, and infant, newborn . Inclusion criteria were articles written in English published between 2010 and 2021 that tested emollients in high-risk infants and measured the development of AD. Results: Eight primary research articles were included. Six studies were limited by small sample sizes, short-term application of emollients, and short-term follow-up. These studies generated inconclusive results. Two large randomized controlled trials (RCTs) with a combined sample of 3, 791 infants found no evidence that early, regular use of emollients prevents AD among high-risk infants. Clinical Implications: Findings from two high-quality RCTs indicate that clinicians should not recommend use of emollients to prevent AD. Clinicians may provide evidence-based recommendations for infant skin care, including bathe with water or a combination of water and liquid cleanser formulated for infants, and avoid soaps. Products applied to skin should be free of scent and contact allergens. Petroleum jelly or mineral oil is appropriate to moisturize infants' skin as needed. Abstract : Atopic dermatitis (AD), also known as eczema, is a common chronic inflammatory skin disorder. Topical emollients have been hypothesized to enhance the skin barrier and therefore be helpful as a preventative measure. In this integrative review, evidence for treating AD is reviewed. Based on findings from two high quality randomized trials, clinicians should not recommend use of emollients to prevent AD. Evidence-based recommendations for infant skin care, includes bathing with water or a combination of water and liquid cleanser formulated for infants, and avoiding soaps. Products applied to skin should be free of scent and contact allergens. Petroleum jelly or mineral oil are appropriate to moisturize infants' skin as needed. Nurses can use these findings to inform their recommendations to parents.